Hubungan Gaya Mengajar Guru dengan Kualitas Belajar Siswa - Zain, Sanjaya Perdana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student learning quality is an important indicator of the effectiveness of the teaching and learning process in schools. However, in junior high school contexts, student learning quality is influenced by various factors, one of which is teachers’ teaching styles. This study aims to examine the relationship between teachers’ teaching styles and student learning quality among seventh-grade students at SMP Babussalam Montong Sari in the 2021/2022 academic year. This study employed a quantitative approach using a correlational research design. The research subjects consisted of 21 seventh-grade students selected through a total sampling technique. Data on teachers’ teaching styles were collected using a Likert-scale questionnaire, while data on student learning quality were obtained from documented academic achievement scores. The research instruments were tested for validity and reliability prior to data collection. Data analysis was conducted using Pearson product–moment correlation and a t-test at a 5% significance level. The results revealed a positive and significant relationship between teachers’ teaching styles and student learning quality, with a correlation coefficient of 0.653, indicating a moderate to strong relationship. The t-test results showed a t-value of 3.72, which was higher than the critical value of 2.86. These findings indicate that better variation in teachers’ teaching styles is associated with higher student learning quality. This study concludes that teachers’ teaching styles play an important role in improving student learning quality, although they are not the sole determining factor.